Antibiotic Resistance: Molecular Mechanisms and Modern Strategies to Limit its Spread - Atiyah, Amidah Ali; Abbas, Wahran Khudhair (Journal of Science in Medicine and Life, 2025)
Antimicrobial resistance (AMR) represents one of the most pressing global health challenges of the 21st century, with over 1.27 million deaths directly attributable to resistant infections annually. This comprehensive review examines the molecular mechanisms underlying antibiotic resistance and evaluates modern strategies developed between 2020-2025 to combat this crisis. The molecular basis of resistance involves sophisticated mechanisms including enzymatic inactivation of antibiotics, target site modifications, efflux pump systems, altered permeability, and biofilm formation. Recent breakthroughs include the structural characterization of the Cfr methyltransferase mechanism conferring broad-spectrum resistance and discovery of novel horizontal gene transfer pathways like vesiduction. Current epidemiological data reveals alarming resistance rates, with 42% median resistance to third-generation cephalosporins in E. coli and 35% methicillin resistance in S. aureus globally. Modern countermeasures encompass revolutionary approaches including AI-driven drug discovery yielding compounds like lariocidin, CRISPR-based antimicrobials entering clinical trials, advanced phage therapy, and microbiome interventions. Antimicrobial stewardship programs have achieved 18% reduction in AMR deaths in developed countries, while rapid diagnostic technologies reduce inappropriate antibiotic use by 11.6%. However, significant challenges persist in implementation, particularly in low-resource settings, and continued innovation in both traditional and alternative therapeutic approaches is essential. The convergence of molecular insights, technological advances, and comprehensive global policies offers unprecedented opportunities to address antimicrobial resistance through evidence-based, coordinated interventions.